To Determine the Correlation between Anthropometric Variables of Obesity and Hypertension at NGMC: A Tertiary Care Hospital - Neupane Pant, Bhawana; Pant, Manoj; Goit, Rajesh Kumar; Neupane, Ashish; Neupane, Ganesh Prasad; Bhargava, Pushpa (Journal of Nepalgunj Medical College, 2018)
Aim: Obesity is associated with the metabolic risk factors such as high blood pressure, body fat abnormality, and glucose intolerance which may influence the morbidity and mortality due to cardiovascular diseases. The present study is to determine the correlation of common anthropometric indices of obesity with blood pressure among population in mid-western region of Nepal. The result will provide us insight on relevant anthropometric indices for predicting hypertension based on linear correlation calculated from our data. Methods: We screened 500 healthy subjects to study the correlation between anthropometric indices and blood pressure. Result: Our result showed strong correlation between Sum of Skin fold, waist circumference, and waist hip ratio with blood pressure (systolic blood pressure, diastolic blood pressure and mean arterial blood pressure). However some of the anthropometric indices like hip circumference and body mass index did not have significant correlation with blood pressure. Conclusion: Provided obesity related morbidity and mortality is burgeoning in our society it is imperative to identify right indicators of cardiovascular disease for specific population. Relevant anthropometric indices can serve as excellent indicators if used based of scientific validation. JNGMC, Vol. 14 No. 2 December 2016, Page:70-74